MALE AND FEMALE STUDENTS’ ATTITUDES TOWARD ENGLISH VOCABULARY MASTERY IN LEARNING SPEAKING (A Survey Study at one of MA Islamic Boarding School in Tasikmalaya) - Prihatini Purbandari; Etika Rachmawati; R. Bunga Febriani (JALL (Journal of Applied Linguistics and Literacy), 2018)
This study aimed to explore the attitudes of Senior High School male and female students toward English vocabulary mastery in learning speaking. This study also investigated the factors influence students’ attitudes toward English vocabulary mastery in learning speaking. Attitude is individual’s response towards an object, inferred from individual’s belief or opinion about it. (Gardner, 1985). The writer conducted the questionnaire to measure the students’ attitudes toward English vocabulary mastery in learning speaking. The writer also interviewed a number of eleventh grade students to explore the factors that affect their attitudes toward English vocabulary mastery in learning speaking. The participants of this study consisted of 58 students of eleventh grade of one of MA Islamic Boarding School in Tasikmalaya. They were 25 male students and 33 female students. These students were purposively chosen. The results of the study showed that most of male and almost all of female students have positive attitude toward English vocabulary mastery in learning speaking. The results also indicated the factors influence their attitudes were their pronunciation, grammar and vocabulary knowledge, their habits speaking English in front of many people, their needs toward English and support from social environment. In conclusion, students’ attitudes toward English vocabulary mastery in learning speaking is important. It helps students improving their English speaking skill. In addition, this study recommends the future research on the same topic can carried out by using other design in order to enrich the development of the theory of attitude. Key words: male and female students, attitude, vocabulary mastery, speaking skill